Enhancing Effect of Hydroxyurea on Hb F in Sickle Cell Disease: Ten-Year Egyptian Experience. (2nd November 2017) - Youssry, Ilham; Abdel-Salam, Amina; Ismail, Rania; Bou-Fakhredin, Rayan; Mohamed Samy, Rania; Ezz El-Deen, Fatma; Taher, Ali T.
Abstract: Patients with sickle cell disease experience hemolytic anemia and vaso-occlusions that result in pain, organ injury, and premature mortality. Several prospective studies have verified the efficacy and tolerability of hydroxyurea (HU), and demonstrated its efficacy in reducing painful vaso-occlusive crises (VOCs) in addition to its ability to increase Hb F levels. We aimed to evaluate the long-term effects of HU therapy on Hb F and assess its long term efficacy and safety in sickle cell disease patients. A retrospective study on 60 sickle cell disease patients was conducted. We studied the laboratory changes, frequency of VOCs per year, frequency of hospital admisions per year and number of transfusions per year, both before and after HU therapy. The follow-up period was 4 to 120 months. Hb F levels after HU therapy positively correlated with the duration of HU therapy, baseline Hb F levels and baseline total hemoglobin (Hb) ( r  = 0.4, p  = 0.04; r  = 0.45, p  = 0.001; r  = 0.5, p  = 0.019, respectively) and inversely correlated with baseline total leucocyte count ( r  = –0.33, p  = 0.034). Hydroxyurea therapy was associated with an increase in the total Hb and mean corpuscular volume (MCV) ( p  = 0.009, p  = 0.000; respectively) and with a decrease in total leucocyte count, platelet count and reticulocyte count ( p  = 0.00, p  = 0.03, p  = 0.02, respectively). Moreover, a significant reduction in the frequency of VOCs, transfusion frequency and hospital admissions per year after HU therapy was shown in the studied subjects. Hydroxyurea induced an increase in Hb F level, which was maintained over time and was associated with clinical efficacy and acceptable safety.